The Positive Impact of Memorizing the Qur'an on the Cognitive Intelligence of Primary School Children - Frananda, Anggra; Niva, Matteson; Maharjan, Kailie (World Psychology, 2024)
Positive impact of learningthafidz is to develop students' ability to memorize and improve students' memorization abilities and can make students more familiar with the teachings of the Islamic religion by memorizing the Qur'an will increase faith, avoid fear, sadness and anxiety, the ability to build better social relationships and gain trust from other people and also know much more about the meaning and significance of each verse he reads. The aim of this research is to determine the positive impact of memorizing Al Quran to improve students' cognitive intelligence at Kinawai Balimbiang Elementary School. To know. Methods used in memorizing the Al-Quran at Kinawai Balimbiang Elementary School. To find out the positive and negative impacts of memorizing the Al-Qur'an at the Kinawai Balimbiang Elementary School. In this research it is known that the programthafidz This is done once a week on Fridays and is carried out at different times for male and female students. Female students carry out the program.thafidz from 10:30-11:30 and for male students men 13:30-14:30. The method used in this research is a qualitative descriptive method by means of interviews and observations.